2015
DOI: 10.5194/acp-15-3045-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pollution controls in Beijing on atmospheric oxygenated volatile organic compounds (OVOCs) during the 2008 Olympic Games: observation and modeling implications

Abstract: Abstract. Oxygenated volatile organic compounds (OVOCs) are important products of the photo-oxidation of hydrocarbons. They influence the oxidizing capacity and the ozone-forming potential of the atmosphere. In the summer of 2008, 2 months of emission restrictions were enforced in Beijing to improve air quality during the Olympic Games. Observational evidence reported in related studies that these control measures were efficient in reducing the concentrations of primary anthropogenic pollutants (CO, NOx and no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 70 publications
(95 reference statements)
4
23
0
Order By: Relevance
“…This suggests that reducing anthropogenic emissions of C 2 H 4 would reduce the HCHO pollution. In comparison, for CH 3 CHO, propene (C 3 H 6 ), i-butene, cis-2-pentene, and i-pentane showed the highest RIR values, which is consistent with previous results suggesting that alkenes and alkanes were the main precursors of CH 3 CHO at an urban site in Beijing (Liu et al, 2015). In terms of CHOCHO, in addition to C 5 H 8 showing the highest RIR, anthropogenic aromatics, especially toluene, also presented a significant contribution.…”
Section: 1002/2017jd027403supporting
confidence: 91%
“…This suggests that reducing anthropogenic emissions of C 2 H 4 would reduce the HCHO pollution. In comparison, for CH 3 CHO, propene (C 3 H 6 ), i-butene, cis-2-pentene, and i-pentane showed the highest RIR values, which is consistent with previous results suggesting that alkenes and alkanes were the main precursors of CH 3 CHO at an urban site in Beijing (Liu et al, 2015). In terms of CHOCHO, in addition to C 5 H 8 showing the highest RIR, anthropogenic aromatics, especially toluene, also presented a significant contribution.…”
Section: 1002/2017jd027403supporting
confidence: 91%
“…Factor 3 is highly loaded with isoprene, monoterpene, and MVK + MACR; all of these species are mostly natural emissions and degradation products (MVK + MACR) (Rinne et al, 2002). It has been reported that isoprene is the major precursor of HCHO, and its contribution to the total HCHO formation was 80-90% in summer in the Southeast U.S. (Marvin et al, 2017;Wolfe et al, 2016), 44% in New York City (Lin et al, 2012), and 30% in Beijing (Liu et al, 2015). Therefore, Factor 3 was identified as a biogenic source.…”
Section: 1002/2017jd027266mentioning
confidence: 99%
“…The toluene / benzene ratio can be used to estimate the contribution of traffic emissions (Schneider et al, 2005). Generally, a value of 1.2-3 is found to be characteristic of vehicular emission in many urban areas (Nelson and Quigley, 1984;Wang et al, 2002;Araizaga et al, 2013). The lower ratio of toluene to benzene (ave. = 2.6) in the SF period suggests that the dominant source is vehicle emission.…”
Section: Emission Ratio Analysismentioning
confidence: 99%